Field monitoring of calcification rates of Mytilus mussels in 2016-2017, South-West Baltic Sea - Sanders, Trystan; Thomsen, Jörn; Müller, Jens Daniel; Rehder, Gregor; Melzner, Frank (In: Sanders, T et al. (2020): Mussel calcification in the Baltic Sea under natural and manipulated carbonate chemistry parameters [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.925017, 2020)
This data set presents data from field monitoring of calcification rates across 15 months from 3 sites in the South-West Baltic Sea (Kiel fjord, Ahrenshoop and Usedom Island). 50 mussels were sampled from settlement structures at each location at 2 - 3 monthly intervals and shell length/mass were recorded over time to estimate calcification rates in the field related to environmental conditions.
Keywords: bicarbonate; calcification; calcium; climate change; ESIR; Omega; Salinity; SIR